2018
DOI: 10.1007/s00383-018-4244-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in pediatric appendicitis is key to a low normal appendix percentage: a national audit on the outcome of appendectomy for appendicitis in children

Abstract: PurposeA laparoscopic approach for emergency appendectomy is increasingly used, in pediatric patients as well. The objective of this study is to audit the current state of diagnostic work-up, surgical techniques and its outcome in children with acute appendicitis.MethodsA prospective consecutive observational cohort study was carried out in a 2-month study period. All patients under 18 years that were operated for suspected acute appendicitis were included. Primary outcome was the infectious complication rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…The finding in this cohort that incidence peaks among persons aged 10-19 years, and is greater among men compared to women, is consistent with previous epidemiological literature [1,32,36,37]. In 2010, a new Dutch guideline on treatment of appendicitis was published, which incorporates ultrasound or CT imaging in the standard diagnostic process [38,39]. It is plausible that fewer patients were operated as a result due to better diagnosis and a fall in the proportion of appendectomy for appendix sana.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding in this cohort that incidence peaks among persons aged 10-19 years, and is greater among men compared to women, is consistent with previous epidemiological literature [1,32,36,37]. In 2010, a new Dutch guideline on treatment of appendicitis was published, which incorporates ultrasound or CT imaging in the standard diagnostic process [38,39]. It is plausible that fewer patients were operated as a result due to better diagnosis and a fall in the proportion of appendectomy for appendix sana.…”
Section: Discussionsupporting
confidence: 86%
“…It is plausible that fewer patients were operated as a result due to better diagnosis and a fall in the proportion of appendectomy for appendix sana. A large Dutch cohort study (n = 1943) performed in 2014 demonstrated a low negative appendectomy rate of 3% [38,39]. Another factor that might play a role is the growing popularity of non-operative treatment and fading dogma 'when in doubt, take it out'.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of these two types varies significantly across ages. In the paediatric population, simple appendicitis accounts for the majority of cases, approximately in 65% [3,4]. For over one hundred years, the appendectomy has been the standard of care for all types of acute appendicitis; however, time has not stood still.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a national audit on the outcome of appendectomy for appendicitis in children showed that preoperative imaging, mainly in the form of ultrasonography, is key to reduce the negative appendectomy rate. 11 This may well be the reason why the majority of respondents rely on this non-invasive form of imaging. Likewise, surgeons seem to be aware of the potential risk of ionizing radiations associated with CT scans, 26 and only rarely rely on this imaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…Following the implementation of these guidelines, two studies have reported a decline in negative appendectomies without an increase in perforation rate. 10,11 Yet, the routine use of imaging to diagnose appendicitis is not unanimously accepted. 12,13 In the last few years, in an effort to evaluate controversial aspects of the management of neonatal and pediatric surgical conditions, the European Paediatric Surgeons' Association (EUPSA) Network Office has administered and analyzed several surveys on the practice patterns of the association members.…”
Section: Introductionmentioning
confidence: 99%